Bom de boca: educação e cultura na cozinha da TV digital - Moraes, Fabiana Cristina Gimenes [UNESP] (2014)
Manifestation of memory and history, the food, which is more natural act; it is social and cultural act. Full of flavors, identities, amoras and knowledge the food is who provides the mass of the roast this work: a thesis dissertation for completion of Masters in Digital TV, also transformed into product: the Bom de boca. Educacional and interactive audiovisual piece, formatted from edutainment, guided by the Historical-critical Pedagogy about culinary culture, the Bom de boca, for the Digital TV. This new medium has its possibilities highlighted here as a resource for the democratization of information, education, and promotion of social inclusion and cultural diversity. While educational and cultural program, the Bom de boca, adapts is to this new scenario. For this, means edutainment while a number of products, programs and media that use methods of entertainment with educational purposes. Its function is to enable learning from the fun, of playfulness. As Historical-critical Pedagogy, it is a pedagogical theory disseminated by Saviani (2009), which relies on the historical materialism, including development of humanity from the material development, and social relations arising from this context. Have the food and all the culinary universe are seen as culture, human production, historical elements and, therefore, fruit of a particular mode of production. It's through the mix between these elements that intended to prove the hypothesis that it is possible to unite them and turn them into a tasty roast in audiovisual format; hat can be used as a learning object, a tool for education. For both, plus the bibliographic research, the work also carried out the production of said audiovisual piece and its evaluation